A Cyp2a polymorphism predicts susceptibility to NNK-induced lung tumorigenesis in mice - Hollander, M.Christine (Oxford University Press, 2011)
Lung tumors from smokers as well as lung tumors from mice exposed to tobacco carcinogens such as 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK), often carry mutations in K-ras, which activates downstream-signaling pathways such as PI3K/AKT/mTOR pathway. Mice with genetic deletion of one of three isoforms of AKT were used to investigate the role of AKT in mutant K-ras-induced lung tumorigenesis in mice. Although deletion of Akt1 or Akt2 decreased NNK-induced lung tumor formation by 90%, deletion of Akt2 failed to decrease lung tumorigenesis in two other mouse models driven by mutant K-ras. Genetic mapping showed that Akt2 was tightly linked to the cytochrome P450 Cyp2a locus on chromosome 7. Consequently, targeted deletion of Akt2 created linkage to a strain-specific Cyp2a5 polymorphism that decreased activation of NNK in vitro. Mice with this Cyp2a5 polymorphism had decreased NNK-induced DNA adduct formation in vivo and decreased NNK-induced lung tumorigenesis. These studies support human epidemiological studies linking CYP2A polymorphisms with lung cancer risk in humans and highlight the need to confirm phenotypes of genetically engineered mice in multiple mouse strains.